(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The article is dedicated to the analysis of PR approaches to reputation management in HR crisis situations, using the example of Russian companies. The paper examines the theoretical foundations of crisis communications and reputation management, as well as the practical application of PR tools in the context of HR crises. Theoretical models of crisis communication (SCCT, image restoration theory) are described, and the main types of HR crises are identified, with examples of practices from Russian companies. Special attention is given to the analysis of successful case studies of companies that effectively dealt with crisis situations related to staff reductions, changes in corporate culture, and other HR challenges. Conclusions are drawn about the need for comprehensive integration of PR and HR functions for effective management of reputational risks.